Pengabdian Kepada Masyarakat Melalui Penyusunan Gambar Denah Gedung Gereja BNKP Hosiana Kota Gunungsitoli - Bimawijaya Laia; Hamedoni Harita; Ikhtiar Aronifati Daeli; Serta Denius Daeli; Muhammad Haris Zalukhu; Envilwan Berkat Harefa; Dermawan Zebua; Andrew Cristopher Harefa; Kevin Berkat Mendrofa; Piter Telaumbanua (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service activity aimed to implement civil engineering expertise through the preparation of a building floor plan for BNKP Hosiana Church in Gunungsitoli City as a technical document to support the planning and development of worship facilities. The partner's main problem was the absence of a systematically documented floor plan, which hindered renovation planning, building development, and the preparation of technical construction documents. The activity employed a participatory approach consisting of coordination with the partner, field surveys, building measurements, data processing, floor plan preparation using AutoCAD software, validation with the church management, and submission of the final technical document. The results demonstrated that an accurate floor plan reflecting the existing building conditions was successfully produced and validated by the church administrators. The document serves as a reference for future renovation planning, building expansion, construction documentation, and systematic building asset management. In addition to producing a technical drawing, the activity improved the partner's understanding of the importance of technical planning documents in supporting effective, efficient, and sustainable building development. This community service demonstrates that the application of civil engineering knowledge can provide practical solutions to community needs through the provision of high-quality technical planning documents.